Put Your Hands In : Poems - Hosea, Chris, 1973- (Book collections on Project MUSE., 2014)
""Exactly a century ago, the Armory Show brought European avant-garde art to New York. We are still experiencing its consequences. Among the works on view was Marcel Duchamp's notorious Nude Descending a Staircase, which a derisive critic wanted to rename 'Explosion in a Shingle Factory.' Both titles come to mind as one reads Chris Hosea's Put Your Hands In, which somehow subsumes derision and erotic energy and comes out on top. Maybe that's because 'poetry is the cruelest month, ' as he says, correcting T.S. Eliot. Transfixed in midparoxysm, the poems also remind us of Samuel Beckett's line).